Study on comparative reeling performance of improved Thai reeling machine and Traditional Ghai reeling machine for quality raw silk production - Alim, Md. Abdul; Ahmed, Faruque; Alam, Md Jahangir (Journal of Scientific Agriculture, 2025)
A Thai reeling machine with (Dual Operative System) has been fabricated at BSRTI for the production of raw silk with high quality and quantity. The experiment was done by four different seasons to determine the cocoon characteristics and reeling performances on the Thai reeling machine. Mean renditta, raw silk recovery (%), reelability (%), waste (%) were found to be 9.74, 71.81%, 63.26% and 5.36%. It was also found that the mean tenacity and elongation percentage were 3.13 (g/d) and 18.74% in the Improved Thai reeling machine, whereas it was 2.87 (g/d) and 18.70% in the Traditional Ghai respectively. BSRTI fabricated an Improved Thai reeling machine (Dual driving system) was suggested as an improved reeling appliance commercially to get high quality raw silk production.